Modification of Gelatin-Methacrylate, Hyaluronic-Methacrylate and Poly(ethylene) glycol Diacrylate hydrogel bioinks towards the additive manufacturing of articular cartilage - Barwick, Matthew William (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Cartilage degradation is most commonly associated with Rheumatoid arthritis and Osteoarthritis, affecting millions of people worldwide. Joint transplants commonly use titanium alloys, which have a shelf life of between 10-15 years. Although the titanium transplant restores partial mobility, side effects such as inflammation, swelling, faulty implants, and metal poisoning in some cases resulting from the transplant. The use of additive manufacturing of articular cartilage sheds new, innovative prospects for joint replacements. This study sets out to formulate and characterize five different hydrogel types towards the additive manufacturing of articular cartilage. Chondrogenic and Adipogenic differentiation was carried out on two separate adipose-mesenchymal stem cell lines A270620-01A, and A311019-02T and validation and efficiency of the differentiation and chondrogenic gene expression was carried out using Alcian Blue stain, Oil Red O stain and Quantitative Reverse Transcription PCR (RT-qPCR). Hydrogel formulation and characterisation of 10 % Gelatin-methacryloyl (GelMA), 10 % Poly (ethylene) glycol diacrylate (PEGDA), 5 % GelMA/5 % PEGDA, 10 % GelMA/0.5 % Hyaluronic Acid Methacrylate (HAMA) and 10 % PEGDA/0.5 % HAMA was carried out through swelling and degradation ratios, surface area and porosity characterisation using Scanning Electron Microscopy (SEM). Hydrogel component and spectroscopic analysis were carried using Real-Time Quantitative Cell Analysis (RTCA) and Fourier-transform Infrared Spectroscopy (FTIR) analysis for each formulated hydrogel's chemical characterisation. Three-dimensional printing (3D) of 10 % PEGDA/0.5 % HAMA and 5 % GelMA/5 % PEGDA was performed using the Zortrax INKSPIRE Resin Ultra-Violet (UV) LCD Desktop 3D Printer. Hydrogel sterility and cell viability were carried out for each hydrogel type using fluorescence microscopy. Both A270620-01A and A311019-02T cell lines showed adipogenic and chondrogenic differentiation ability, with A311019-02T cell line showing greater chondrogenic differentiation of Alcian blue staining. The A270620-01A cell line resulted in a greater collagen gene expression based on the RT-qPCR results. The hydrogel 10 % GelMA showed the greatest swelling ratio of 1260 % in DPBS and 1192 % in DMEM. A significant difference between hydrogel swelling and swelling with Dulbecco's Phosphate Buffered Saline (DPBS) and Dulbecco's Modified Eagle Medium (DMEM) was observed. The 10 % PEGDA hydrogel had the greatest degradation ratio of 59 % mass remaining, where the 10 % GelMA/0.5 % HAMA showed the least amount of degradation with a mass remaining at 91 %. The 10 % GelMA showed the greatest porosity will the largest pore size of 14 Î¼m in diameter. Hydrogel component and spectroscopic analysis showed no cytotoxic effects for the visible light photoinitiator used to polymerize the hydrogel and no cytotoxic effects for the concentrations used in chondrogenic differentiation. The FTIR analysis showed partial gelatin and hyaluronic acid modification with methacrylic anhydride; however, the distinction between the hybrid hydrogels and single polymer hydrogels could not be made effectively. UV and ethanol washing showed to completely sterilise the hydrogel disks from any contaminants, making them suitable for tissue culture. The cell viability analysis showed the 10 % GelMA/HAMA having the highest cell viability of 77.3 % using 5000 cells/disk and 89.64 % viability using 50 000 cells/disk over a 7-day incubation period. Overall, the combination of two polymers, GelMA and HAMA, has good potential as a 3D hydrogel scaffold towards additive manufacturing of articular cartilage.
Keywords: Cartilage -- Diseases; Cartilage -- Regeneration; Articular cartilage -- Diseases; Chondrogenesis; Stem cells; Scanning electron microscopy; Fourier transform infrared spectroscopy; Three-dimensional printing; Gelatin-Methacrylate; Hyaluronic-Methacrylate; Poly(ethylene) glycol; Diacrylate; Hydrogel bioinks; Real-Time Quantitative Cell Analysis (RTCA); Bioprinting